Digital forvaltning ved planlægning af arealdrift i Skov- og Naturstyrelsen - Andersen, Bent Egede; Buttenschøn, Christopher; Dralle, Kim; Friese, Søren; Retsloff, Thomas; Skyum, Jørgen (Geoforum Perspektiv, 2012)